STUDI KASUS PERILAKU DAKTILITAS STRUKTUR BANGUNAN 20 LANTAI TERHADAP DEFISIENSI MUTU BETON MENGGUNAKAN METODE PUSHOVER - Arissaputra, Sofian; Irwan, Josia (Technologic, 2025)
Concrete strength deficiency in building affects structural ductility. This study aims to evaluate the ductility of structures when using the designed concrete strength and to assess the impact when concrete experiences deficiencies. The analysis involves three building with varying width-to-length ratios, identified as buildings A, B, and C. The width-to-length ratios are 1:3 for building A, 1:4 for building B, and 1:5 for building C. Each building model is analyzed using four uniform concrete strengths: 25 MPa as the design strength, followed by 20, 15, and 10 MPa. Structural ductility is determined using nonlinear static (pushover) analysis with ETABS software, based on the seismic design provisions of SNI 1726:2019. From this, the structural response modification factor (R) can be obtained. The average ductility results from all models show a linear decrease to the reduction in concrete strength. Regarding the effect of span ratio, there is a tendency for ductility to decrease as the building becomes more elongated. The percentage reduction in ductility from 25 to 10 MPa is 39% for building A, 46% for building B, and 50% for building C. The ductility and R values at 15 and 10 MPa fall below the minimum requirements specified in SNI 1726:2019.